KAJIAN KOSEPTUAL TENTANG PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PAI DI ERA PENDIDIKAN ABAD 21 - Prasahaja, Ferdi; Halisaturrohma, Siti Nur; Rodhliyah, Nur Eisyatur; Muhammad, Devy Habibi (Institut Binamadani Indonesia, 2026)
The development of digital technology and the demands of 21st-century skills place Islamic Religious Education (PAI) teachers in a strategic position to enhance their professionalism and the quality of learning. Teachers are expected not only to master the four basic teaching competencies but also to adapt to technological changes and implement learning approaches relevant to the needs of today's students. This research aims to describe the development of professional competence of PAI teachers in the 21st-century education era through a comprehensive literature review. The method used is a literature study, examining national and international journals, educational policy documents, and various research related to digital literacy, Continuing Professional Development (CPD), and the Learning Cycle 5E model. The analysis process was conducted descriptively to synthesize theoretical and empirical findings regarding the challenges, opportunities, and strategies for strengthening the competence of PAI teachers. The study results indicate that although PAI teachers understand the importance of 21st-century skills, their implementation remains limited due to low digital literacy and a lack of technology training. CPD, ICT integration, and the application of the Learning Cycle 5E model have been proven to support the improvement of students' pedagogical abilities and critical thinking. This research contributes to strengthening the theoretical framework regarding the professionalism of PAI teachers and provides practical implications for developing sustainable competencies that are adaptive to the demands of the modern era.